Data Acquisition for Search, Rescue and Relief Operation in Affected Areas Caused by Natural Disaster - Sharma, Rabin Kaji (Journal on Geoinformatics, Nepal, 2016)
Nepal is vulnerable to number of disaster and consequently has to bear loss of properties and infrastructures as well as human and cattle lives. In such circumstances, responsible authority should response for search, rescue and relief operation for the affected people due to disaster. In order to perform this job, they need spatial data of the affected areas and social data and information related to the disaster. There are several options for acquisition of such data and this paper tries to recommend for adopting a suitable mechanism. Every part of the world would experiences disaster either due to natural phenomenon or due to human negligence. Bigger the magnitude of the disaster, bigger will be the amount of destruction. When there is loss or damage of the properties, infrastructures and lives then responsible authority should assess the damage and should act promptly to support the affected people and should prepare plan to stabilize the situation caused by the disaster. Basis to prepare the plan is the data and information collected aftermath of the disaster. There are several methods for collection and should choose the appropriate mechanism so that the necessary data and information should be collected in a short span of time, should obtain reliable data and information and the procedure should be economical. Based on the data and information collected, the responsible organization should response for the search, rescue and relief operation.